Ritmo diário das atividades externas de Nannotrigona testaceicornis (Lepeletier, 1836) (apoidea, apidae) e a influência dos fatores ambientais e meteorológicos, em uma área da Chapada Diamantina, Bahia - Silva, Wagner Pereira (2012)
Flight activities stingless bee are associated to a variety of behaviors, in particular gathering pollen, nectar, resin and mud throughout the day, which can be influenced by extrinsic factors (abiotic) or intrinsic (internal conditions of the colony, morphology and physiology of individuals). The present study aimed to analyze the daily rhythm of external activities of Nannotrigona testaceiconis and the influence of environmental and meteorological factors on these activities in the Chapada Diamantina, Bahia, Brazil. The field study was conducted bimonthly between outubro/10 and outubro/11 for three consecutive days (between 5:00 and 19:00 h), in two colonies (one natural and one managed), considering the data of temperature, relative humidity and light intensity. The activity of the colony managed is higher than the natural colony in all months. Despite this, both colonies showed regularity with regard to the first times of the activities and also with respect to acrophases for most of the analyzed activities, which have generally occurred in the morning. The daily flight activity rhythm of both bee colonies was synchronized by light / dark daily and photoperiodic annual cicles which can act as entrainers of the rhythm. Also, the rhythm of external flight activities was influenced by temperature and light intensity that can act as modulators.